2020
DOI: 10.3390/ani10101846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Optimal Carbohydrase Mixtures on Nutrient Digestibility and Digestible Energy of Corn- and Wheat-Based Diets in Growing Pigs

Abstract: This study aimed to evaluate the effects of optimal carbohydrase mixture (OCM) on macronutrients and amino acid digestibility and the digestible energy (DE) in growing pigs fed the corn-soybean meal-based diet (CSM) and the wheat-soybean meal-based diet (WSM). A total of 36 ileal-cannulated pigs (50.9 ± 4.9 kg initial body weight) were allotted to four dietary treatments randomly, which included CSM and WSM diets, and two diets supplied with corresponding OCM. These OCMs were screened using an in vitro method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…A previous study reported that diet type did not influence ADG, but growing pigs fed corn–soybean meal diets from days 0 to 64 had decreased ADFI and increased G:F compared to the pigs fed 30% dried distillers grains with solubles and 19% wheat middling diets during this period [ 16 ]. The apparent ileal digestibilities of dry matter, neutral detergent fiber, and gross energy (GE) of growing pigs fed a corn-based diet were similar to those of pigs fed a wheat-based diet [ 17 ]. Weaned pigs that were fed maize-based diets had a 60 g higher ADG than pigs that were fed wheat–barley-based diets, even though the daily feed intake was similar because of higher N retention [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that diet type did not influence ADG, but growing pigs fed corn–soybean meal diets from days 0 to 64 had decreased ADFI and increased G:F compared to the pigs fed 30% dried distillers grains with solubles and 19% wheat middling diets during this period [ 16 ]. The apparent ileal digestibilities of dry matter, neutral detergent fiber, and gross energy (GE) of growing pigs fed a corn-based diet were similar to those of pigs fed a wheat-based diet [ 17 ]. Weaned pigs that were fed maize-based diets had a 60 g higher ADG than pigs that were fed wheat–barley-based diets, even though the daily feed intake was similar because of higher N retention [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fecal samples (100 g per pig) were collected for three consecutive days from the rectum after pigs had free access to their diet for 30 min. All fecal samples were fixed with 10% dilute hydrochloric acid and toluene, then stored at −20 °C prior to analysis [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tyler mill for chemical analysis. Proximate analysis of the experimental diets and feces samples were performed using standard Association of Official Analytical Chemists methods [ 18 ]. The samples were dried at 105 °C in a drying oven to a constant weight to determine dry matter (DM) content.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These complex carbohydrates pose a digestive challenge as pigs inherently lack the enzymes necessary for their breakdown, leading to fermentation and gas production [ 49 , 50 ]. Zhang et al [ 51 ] further explain that microbial fermentation of these undigested proteins and amino acids in the hindgut contributes significantly to ammonia production, a major component of the overall ammonia emission in manure. The beneficial impact on nutrient digestion and gas emission reduction [ 49 , 50 ].…”
Section: Dietary Enzymesmentioning
confidence: 99%